2019
DOI: 10.3126/jpahs.v6i2.27234
|View full text |Cite
|
Sign up to set email alerts
|

Stigma perceived by family members of psychiatric patients attending outpatient department of a teaching hospital

Abstract: Introductions: Stigma and unfavorable view of people towards mental illness is prevailing in Nepal due to lack of awareness. Stigma among family members of people with mental illness has a serious impact on the outcome. This study aims to identify the level of perceived stigma by family members and association with selected demographical variables. Methods: A cross-sectional research design was used to assess the stigma perceived by family members of patients visiting psychiatry outpatient department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…This means that the caregivers felt stigmatised while caring a relative with mental illness. The findings of this study were in line with the study conducted in Nepal (2019), 11 (2014), 12 and Vellore, India (2019) 10 which showed that caregivers felt burden and stigma having a relative with mental illness.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This means that the caregivers felt stigmatised while caring a relative with mental illness. The findings of this study were in line with the study conducted in Nepal (2019), 11 (2014), 12 and Vellore, India (2019) 10 which showed that caregivers felt burden and stigma having a relative with mental illness.…”
Section: Discussionsupporting
confidence: 90%
“…Convenience sampling technique was used while selecting the caregivers of mentally ill patient. Two hundred and seventeen caregivers were included in the study after taking the prevalence of perceived stigma as 83%, statistical formula of n= Z 2 pq/d 2 , where d (allowable error) = 0.05, z (confidence level) = 1.96, p (prevalence of perceived stigma) 11 = 0.83 and q (1-p) = 0.17 but one of the respondent withdrew from the study thus 216 caregivers were taken. Data was collected using face to face interview technique from either of parents, siblings, family members and friends aged above 18 years whose duration of stay with the patient should be at least six months.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the qualitative studies with stigma as the major theme or domain focused on public stigma of either general community members or healthcare workers. Quantitative or mixed methods studies predominantly focused on self or internalised stigma of people with lived experiences of mental disorders (PWLE) (Adhikari, 2015; Neupane et al ., 2016; Amatya et al ., 2018; Rathod et al ., 2018; Maharjan and Panthee, 2019; Shrestha, 2019), public stigma (family and community members) (Neupane et al ., 2016; Amatya et al ., 2018; Koirala et al ., 2019; Luitel et al ., 2019; Pandey, 2019), health workers’ stigma (Gartoulla et al ., 2015; Pathak and Montgomery, 2015; Kohrt et al ., 2018 b , 2020), medical and pharmacy students’ stigma (Panthee et al ., 2010; Adhikari, 2018; Jalan, 2018; Shakya, 2018), and perceived stigma among PWLE and family members (Adhikari et al ., 2008; Lamichhane, 2019). Four studies exclusively focused on courtesy stigma (Angermeyer et al ., 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Health workers reported that mental disorders were life-long conditions that had no effective treatment. The general public stated that mental disorders could not be cured by Western biomedicine but only through traditional healing (Kisa et al ., 2016; Simkhada et al ., 2016; Koirala et al ., 2019; Lamichhane, 2019; Kaiser et al ., 2020). This was also reflected in conceptions about the use of psychotropic medications for mental health conditions; most people described that once a person starts taking medications, she/he must take it for life (Upadhaya et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation